Low Ozone Over Southern Australia in August 2011 and its Impact on Solar Ultraviolet Radiation Levels. (20th May 2013) - Gies, Peter; Klekociuk, Andrew; Tully, Matthew; Henderson, Stuart; Javorniczky, John; King, Kerryn; Lemus‐Deschamps, Lilia; Makin, Jennifer
Abstract During August 2011 stratospheric ozone over much of Southern Australia dropped to very low levels (approximately 265 Dobson Units) for over a week above major population centers. The weather during this low ozone period was mostly clear and sunny, resulting in measured solar ultraviolet radiation (UVR) levels up to 40% higher than normal, with UV Index > 3 despite being winter. Satellite ozone measurements and meteorological assimilated data indicate that the event was likely due in large part to the anomalous southward movement over Australia of ozone‐poor air in the lower stratosphere originating from tropical latitudes. At the time, a study measuring the UVR exposures of outdoor workers in Victoria was underway and a number of the workers recorded substantial UVR exposures and were sunburnt. Given the cities and populations involved (approximately 10 million people), it is likely that many people could have been exposed to anomalously high levels of solar UVR for that time of year, with resultant higher UVR exposures and sunburns to unacclimatized skin (often a problem transitioning from low winter to higher spring UVR levels). Reporting procedures have been modified to utilize ozone forecasts to warn the public of anomalously high UVR levels in the future.